Strategi Pengembangan Pertanian Berbasis Komoditas Lokal: Studi Kasus Pada Komoditi Jeruk Di Desa Jujun Kecamatan Keliling Danau Kabupaten Kerinci - Muchlis, Fuad; Lizawati, Lizawati; Tafzi, Fitry; Effran, Endy (Balitbangda Provinsi Jambi, 2024)
This research aims to 1) describe the description of local orange farming in Jujun Village, Keliling Danau District, Kerinci Regency, 2) formulate a strategy for developing local orange commodities in Jujun Village, Keliling Danau District, Kerinci Regency, 3) analyze alternative strategies for developing local oranges in Jujun Village, Keliling District Kerinci Regency Lake. The analytical method used is descriptive analysis with IFAS, EFAS and SWOT analysis. The results of this research show that (1) the productivity of local orange farming in the study area fluctuates, (2) internal factors (strengths and weaknesses), and external factors (opportunities and threats) in local orange farming are in quadrant I position, indicating an organization that strong and has opportunities, so that it becomes the most profitable position for farmers, (3) alternative strategies that can be recommended are progressive strategies, namely cultivating and providing assistance to farmers to strengthen farmer institutions, Support and facilitation to support the availability of agricultural facilities and infrastructure, Encourage farming To maximize the use of political land, Collaboration with Meldia introduces products, facilitates capital assistance from financing institutions, and encourages improvements in the quality and quantity of farming roads, especially in local orange production center locations